(untitled) (International Journal of Innovative Technologies in Economy, 2018)
The article analyzes the state and dynamics of modern functioning of the financial market of Ukraine, development of legislative, normative and institutional support for realization of the strategy of development of the domestic financial sector in the conditions of an open economic system. Some indicators of activity of banking and non-bank lending institutions were characterized and key problems of their functioning were determined. It has been established that medium- and long-term fiscal policy is dependent on the development of the financial sector, in particular the stock market. The lack of reliable instruments on the domestic securities market is identified, which is a deterrent to the development of institutional participants and hinders the development of the entire financial market. It is substantiated that further development of the financial sector requires strategic measures for its improvement, the definition of a single policy on the development of the financial market at the state level, a reorientation to the creation of domestic investment sources, increased transparency in the adoption of regulatory decisions and the role of associations of market entities, etc. It is noted that the key to stabilization and economic revival of the country is the creation of an effective system of control over the management of national resources and public finances. Corrective actions are proposed to develop the institutional structure of the market, develop its infrastructure, protect shareholders’ rights, increase transparency and introduce effective and open regulatory policy and appropriate supervision. Also, a number of measures were proposed for successful implementation of Ukraine’s European integration in the financial sector and, in the long run, to ensure macroeconomic stability in Ukraine under the conditions of an open economic system.